2022
DOI: 10.3390/ijms231710046
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in Postharvest Senescence of Fruits

Abstract: Nitric oxide (NO) acts as a gaseous signalling molecule and is considered to be a key regulator in the postharvest storage of fruits. Postharvest senescence is one of the most serious threats affecting the usage and economic value of fruits. Most recent studies have found that exogenous NO application can effectively improve the quality and prolong the shelf life of fruit postharvest by inhibiting postharvest diseases and alleviating chilling injury. Understanding the roles of NO is essential to elucidating ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…The senescence of postharvest fruits and vegetables is considered an irreversible biological process that consumes nutrients until cell death [47]. Fruits and vegetables undergo aerobic respiration as they ripen and age, and it is the main energy source for their cells during this process [48].…”
Section: Physiological and Nutritional Quality Changesmentioning
confidence: 99%
“…The senescence of postharvest fruits and vegetables is considered an irreversible biological process that consumes nutrients until cell death [47]. Fruits and vegetables undergo aerobic respiration as they ripen and age, and it is the main energy source for their cells during this process [48].…”
Section: Physiological and Nutritional Quality Changesmentioning
confidence: 99%
“…Therefore, SNP has been utilised as an alternative NO exogenous donor, which is soluble in water and releases NO gas, to achieve expected concentrations (Pols et al, 2022). It has been found that the beneficial consequences of exogenous NO treatments on fruit and vegetables are concentration dependent, and optimal concentration varied with varieties and cultivars (Li et al, 2022a). Aghdam et al (2019) reported that 500 μM SNP treatment could maintain the firmness of cherry fruits, delay the browning of cherry flesh, promote the accumulation of phenolics, flavonoids and anthocyanins and improve DPPH clearance compared with 250 and 1000 μM treatment during the storage of 21 days at 4 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SNP has been utilised as an alternative NO exogenous donor, which is soluble in water and releases NO gas, to achieve expected concentrations (Pols et al ., 2022). It has been found that the beneficial consequences of exogenous NO treatments on fruit and vegetables are concentration dependent, and optimal concentration varied with varieties and cultivars (Li et al ., 2022a). Aghdam et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nitric oxide synthase and its action mechanism in plants needs to be further studied. Importantly, the effectiveness of nitric oxide treatment on preserving the quality depends on the species of fruits and vegetables, the concentration, and form (e.g., liquid or gaseous) of nitric oxide applied (Chaki et al, 2015;Rodriguez-Ruiza et al, 2019;Gonzalez-Gordo et al, 2019;Shi et al, 2019;Li et al, 2022;Liu et al, 2023).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%